An Innovative Hangboard Design to Improve Finger Strength in Rock Climbers. (2016) - Anderson, Michael L.; Anderson, Mark L.; Sanders, Adam
Abstract: In elite rock climbing, finger strength is critical, and is directly related to performance. A hangboard, composed of sets of artificial climbing grips to hang from, is often used by climbers to improve their finger strength. While some research has studied training protocols for climbing, virtually no published research exists addressing the specific enhancement of training equipment to improve training effectiveness. Here we seek to show that hangboard design, especially novel features included in the Rock Prodigy Forge hangboard increases the effectiveness of hangboard training. Recently, this hangboard was developed through an iterative process leveraging modern CAD/CAM techniques. This enabled design engineers to optimize the hangboard for improved training benefit and reduced injuries. As a result, several innovative features were added to the design including: (a) equation-driven grip edge profiles, (b) drafted pockets, (c) novel grip designs, (d) improved grip geometry, and (e) improved texture, among other features. The Forge was tested by experienced climbers, and 92% assessed it as more effective than other training tools, with 91% of users able to train harder without fear of injury relative to other training methods, and 86% reporting improved climbing performance. This is a significant and unique result for the sport of climbing.